Consideracóes sobre forrageio arbóreo por Scarabaeidae (Coleoptera, Scarabaeoidea), e dados sobre sua ocorréncia em floresta tropical do Brasil - Vaz de Mello, Temando Z.; Louzada, Júlio N. C. (Instituto de Ecología, A.C., 1997)
Possible relations ,among perching, arboreal foraging and phoresy with arbórea! mammals are proposed, A summary of current data on arboreal foraging of tropical rainforest dung beetles is given, and new data are presented. Canthon (Glaphyrocanthon) sp., Sylvicanthon foveiventre (Schmidt, 1934), Parahyboma furcatum (Laporte, 1840) and Canthidium sp. are reportad from human feces and carcass baited traps at 10 m high inside Atlantic Semideciduous Rainforest from Vicosa, State of Minas Gerais, southeastern Brazil.